Breast Milk Feeding Rates in Patients with Cleft Lip and Palate at a North American Craniofacial Center. (May 2017) - Alperovich, Michael; Frey, Jordan D.; Shetye, Pradip R.; Grayson, Barry H.; Vyas, Raj M.
Objective: Our study goal was to evaluate the rates of breast milk feeding among patients with oral clefts at a large North American Craniofacial Center. Methods: Parents of patients with oral clefts born from 2000 to 2012 and treated at our center were interviewed regarding cleft diagnosis, counseling received for feeding, and feeding habits. Results: Data were obtained from parents of 110 patients with oral clefts. Eighty-four percent of parents received counseling for feeding a child with a cleft. Sixty-seven percent of patients received breast milk for some period of time with a mean duration of 5.3 months (range 0.25 to 18 months). When used, breast milk constituted the majority of the diet with a mean percentage of 75%. Breast milk feeding rates increased successively over the 13-year study period. The most common method of providing breast milk was the Haberman feeder at 75% with other specialty cleft bottles composing an additional 11%. Parents who received counseling were more likely to give breast milk to their infant ( P = .02). Duration of NasoAlveolar Molding prior to cleft lip repair did not affect breast milk feeding length ( P = .72). Relative to patients with cleft lip and palate, patients with isolated cleft lip had a breast milk feeding odds ratio of 1.71. Conclusion: We present breast milk feeding in the North American cleft population. Although still lower than the noncleft population, breast milk feeding with regards to initiation rate, length of time, and proportion of total diet is significantly higher than previously reported.